2009
DOI: 10.1002/lary.20164
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the bone‐anchored hearing aid for single‐sided deafness

Abstract: Our results show short- and long-term efficacy for the BAHA in adults with single-sided deafness for recognition of speech in noise (noise in front, speech lateralized to the bad ear) and on subjective measures of benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 9 publications
7
67
4
2
Order By: Relevance
“…A significant improvement of j1.65 dB SNR was found for situation 3. This improvement is lower compared with findings with a BAHA system that reported improvements of j2.1 to j3.9 dB (29Y31) (8). One reason for this difference may be the setting of the microphone (omnidirectional) compared with a directional microphone mode.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…A significant improvement of j1.65 dB SNR was found for situation 3. This improvement is lower compared with findings with a BAHA system that reported improvements of j2.1 to j3.9 dB (29Y31) (8). One reason for this difference may be the setting of the microphone (omnidirectional) compared with a directional microphone mode.…”
Section: Discussioncontrasting
confidence: 56%
“…The main drawback is that the better ear must also be fit with a device in addition to the deaf ear, where the microphone is located (5,6); 2) Bone-anchored hearing aid systems transmit sound to the better side by bone conduction (BC). This technique was introduced in 1977 (7) and was originally used for conductive and mixed hearing losses before the indication was expanded for use with SSD, and Food and Drug Administration approval was acquired in 2002 (8). Several studies have shown significant speech understanding improvement and improvement of quality of life for SSD (9Y13); 3) Nonsurgical removable BC prosthetic hearing devices transmit sound via the teeth (14); 4) The cochlear implant is an invasive option with the goal of restoring true binaural hearing.…”
mentioning
confidence: 99%
“…12; SNR S0N90: 23.5 dB). In other studies that evaluated the effect of a bone-anchored hearing aid in singlesided deafness (which is a similar situation to our 1-sided CI patients), deterioration in situation S0N90 was -0.7 to -2.5 dB [Bosman et al, 2003;Hol et al, 2004;Linstrom et al, 2009;Pfiffner et al, 2011]. Our value of -0.66 lies at the bottom end of the scale of the quoted studies.…”
Section: Discussionmentioning
confidence: 65%
“…Bisher erfolgte die Versorgung einseitig tauber Personen mittels CROS-Hör-geräten ("contralateral routing of signal") oder der BAHA-CROS-Technik ("bone anchored hearing aid"; [9,10]). Ungleich erfolgreicher kann ein ertaubtes Ohr mittels Cochleaimplantat (CI) behandelt werden, da dies die verlorene Funktion wiederherstellen kann.…”
Section: Audiologische Ergebnisse Mit Cochleaimplantat Bei Einseitigeunclassified